2021
DOI: 10.1038/s41388-021-01800-x
|View full text |Cite
|
Sign up to set email alerts
|

C/EBPβ is a MYB- and p300-cooperating pro-leukemogenic factor and promising drug target in acute myeloid leukemia

Abstract: Transcription factor MYB has recently emerged as a promising drug target for the treatment of acute myeloid leukemia (AML). Here, we have characterized a group of natural sesquiterpene lactones (STLs), previously shown to suppress MYB activity, for their potential to decrease AML cell proliferation. Unlike what was initially thought, these compounds inhibit MYB indirectly via its cooperation partner C/EBPβ. C/EBPβ-inhibitory STLs affect the expression of a large number of MYB-regulated genes, suggesting that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 59 publications
0
16
0
Order By: Relevance
“…We have previously observed that small-molecule mediated inhibition of transcription factor C/EBPβ exerted similar effects on MYB-regulated genes and caused comparable biological effects in AML cells as inhibition of MYB itself [ 37 , 42 , 45 ]. This led us to propose that MYB acts in concert with C/EBPβ and p300 to form a “transcriptional module” that controls the expression of genes involved in maintaining AML cells in an undifferentiated state [ 45 ]. Support for this idea came from the analysis of the GFI1 gene, whose expression is required for the maintenance of hematopoietic stem and progenitor cells [ 54 , 55 , 56 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We have previously observed that small-molecule mediated inhibition of transcription factor C/EBPβ exerted similar effects on MYB-regulated genes and caused comparable biological effects in AML cells as inhibition of MYB itself [ 37 , 42 , 45 ]. This led us to propose that MYB acts in concert with C/EBPβ and p300 to form a “transcriptional module” that controls the expression of genes involved in maintaining AML cells in an undifferentiated state [ 45 ]. Support for this idea came from the analysis of the GFI1 gene, whose expression is required for the maintenance of hematopoietic stem and progenitor cells [ 54 , 55 , 56 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…Support for this idea came from the analysis of the GFI1 gene, whose expression is required for the maintenance of hematopoietic stem and progenitor cells [ 54 , 55 , 56 , 57 ]. We showed that GFI1 expression is regulated in a direct manner via MYB and C/EBP binding sites in the GFI1 promoter through the cooperation of MYB, C/EBPβ, and p300 [ 45 ]. To examine if Bcr-TMP disrupts the function of this module in AML cells we compared the effect of Bcr-TMP on HL60-control cells and HL60 cells expressing ectopic C/EBPβ.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations